How do you solve #3(-2 - 3x) = -9x - 4 #?

1 Answer
May 26, 2018

Answer:

NO SOLUTION or #cancel(0)#

Explanation:

First, use the distributive property shown below to simplify #3(-2-3x)#:
cdn.virtualnerd.com

Following this image, we can expand it:
#color(blue)(3(-2-3x) = (3 * -2) + (3 * -3x) = -6 - 9x)#

Put it back into the equation:
#-6-9x = -9x - 4#

Add #color(blue)(9x)# to both sides of the equation:
#-6 - 9x quadcolor(blue)(+quad9x) = -9x quadcolor(blue)(+quad9x) - 4#

#-6 = -4#

However, now we have no more variables!

Now we have to see whether the left hand side equals to the left hand side. #-6# does NOT equal to #-4#, therefore, the answer is NO SOLUTION or #cancel(0)#.

Hope this helps!